Sonochemical degradation of ofloxacin in aqueous solutions - Achilleos, Antigoni; Papaioannou, Agelos B.; Valanidou, Lilian (My University, 2010)
The use of low frequency (20 kHz), high energy ultrasound for the degradation of the antibiotic ofloxacin in water was investigated. Experiments were performed with a horn-type ultrasound generator at varying applied power densities (130-640 W/L), drug concentrations (5-20 mg/L), hydrogen peroxide concentrations (0-100 mM) and sparging gases (air, oxygen, nitrogen and argon). In general, conversion (which was assessed following sample absorbance at 288 nm) increased with increasing ultrasound energy and peroxide concentration and decreasing initial drug concentration. Moreover, reactions under an argon atmosphere were faster than with diatomic gases, possibly due to argon's physical properties (e.g. solubility, thermal conductivity and specific heat ratio) favoring sonochemical activity. Overall, low to moderate levels of ofloxacin degradation were achieved (i.e. it never exceeded 50%), thus indicating that radical reactions in the liquid bulk rather than thermal reactions in the vicinity of the cavitation bubble are responsible for ofloxacin degradation.
Keywords: Degradation; Ofloxacin; Ultrasound; Water